2005
DOI: 10.1093/nar/gni085
|View full text |Cite
|
Sign up to set email alerts
|

A versatile reducible polycation-based system for efficient delivery of a broad range of nucleic acids

Abstract: Synthetic vectors based on reducible polycations consisting of histidine and polylysine residues (HIS RPCs) were evaluated for their ability to deliver nucleic acids. Initial experiments showed that RPC-based vectors with at least 70% histidine content mediated efficient levels of gene transfer without requirement for the endosomolytic agent chloroquine. Significant gene transfer was observed in a range of cell types achieving up to a 5-fold increase in the percentage of transfected cells compared to 25 kDa PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
192
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(199 citation statements)
references
References 52 publications
5
192
2
Order By: Relevance
“…Since Boussif et al(1995) hope for non-viral vector in gene delivery, PEI has become the golden criteria in the field of non-viral gene transfer vectors (Read et al, 2005b). To make PEI more suitable for gene therapy, modifying PEI with ligands is one of the useful strategies, targeting specially to the receptors on cell membrane to improve the targeting ability of PEI.…”
Section: Discussionmentioning
confidence: 99%
“…Since Boussif et al(1995) hope for non-viral vector in gene delivery, PEI has become the golden criteria in the field of non-viral gene transfer vectors (Read et al, 2005b). To make PEI more suitable for gene therapy, modifying PEI with ligands is one of the useful strategies, targeting specially to the receptors on cell membrane to improve the targeting ability of PEI.…”
Section: Discussionmentioning
confidence: 99%
“…Also, different dithiol-bearing groups, e.g. nuclear localization sequences comprising two cysteine residues, can be incorporated in the oxidation reaction, giving rise to disulfide-containing copolymers with multiple functionalities (Read et al, 2005).…”
Section: Preparation Of Bioreducible Cationic Polymers As Non-viral Gmentioning
confidence: 99%
“…D,L -Buthionine sulfoxamine (BSO), a known GSH inhibitor, was used as previously described by Read et al [22]. H9C2 cells were plated 48 hrs prior to BSO treatment at 1.0 × 10 5 cells/ well in 6-well plates.…”
Section: Gsh Inhibitionmentioning
confidence: 99%
“…Seymour and coworkers showed that the intracellular levels of glutathione (GSH) affected nucleic acid delivery of their reducible polycations [22]. Previous work in mouse fibroblast cells also showed that upon internalization of SS-PAEI complexed with fluorescent labeled pDNA, complexes showed a wider dispersion of pDNA as compared to a non-reducible bPEI control.…”
Section: Ss-paed Mediated Gene Delivery Is Dependent On Glutathionementioning
confidence: 99%